Physico-chemical and functional properties of grain tef [ Eragrostis tef (Zucc.) Trotter] starch - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2013)
Thesis (DPhil (Food Science))--University of Pretoria, 2006.